Pengaruh Store Atmosphere dan Harga terhadap Revisit Intention Konsumen pada Kawisari Coffee dan Eatery Jakarta - Antonius, Leon; Facrureza, Dewanta (MES Management Journal, 2024)
Food and beverages are a component of the tourism industry that draws people to a location. Price and the atmosphere of the store, in addition to taste and product quality, can influence a customer's decision to shop. Kawisari Coffee & Eatery is a food and beverage retailer based in Jakarta. Many people who went to Kawisari Coffee & Eatery Jakarta had bad experiences because the hot environment made them feel uncomfortable and the prices weren't what they expected. Their decision to return may be influenced by this. The motivation behind this examination is to figure out how clients' expectations to get back to Kawisari Espresso and Restaurant Jakarta are impacted by the shop environment and costs. This study used quantitative descriptive methods. The sample for this study consists of customers who have made purchases at Kawisari Coffee & Eatery Jakarta. To gather information, polls were disseminated to 100 respondents utilizing the purposive inspecting methodology. SPSS Experiences 25 was used to play out different straight backslide examination on the data. With a normal t worth of 4.473 which is more unmistakable than the t table of 1.661 and a significance level of 0.000 which is more noticeable than 0.05, this investigation shows that (1) shop air basically influences plan to get back to. (2) Cost influences mean to get back to, with a basic worth of 0.317 more conspicuous than 0.05 and a normal t worth of 1.005 t table of 1.661. (3) The goal is to return to the combination of store climate and cost impacts, with an expected f-count value of 10.419 higher than the f-table value of 3.09 and an importance level of 0.000 higher than 0.05. The ideas that can be given for Kawisari Espresso and Restaurant Jakarta are to expand the quantity of climate control systems to keep clients from feeling overheated and focusing entirely on reasonable and cutthroat costs for clients to increment client encounters and animate client interests to visit once more.